1988
DOI: 10.1039/c39880000619
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of mangostin: the origin of the xanthone skeleton

Abstract: Cinnamic, benzoic, and m-hydroxybenzoic acids and benzophenone (1) are efficient precursors to mangostin (3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 1 publication
1
28
0
Order By: Relevance
“…1, compound 7) was identified also in Garcinia mangostana (Hypericaceae) [22]. Cinnamic acid, benzoic acid, m-hydroxybenzoic acid and malonic acid were found to be efficient precursors of this compound [22].…”
Section: Hypothetical Biosynthesis Pathway Of Xanthonesmentioning
confidence: 93%
See 1 more Smart Citation
“…1, compound 7) was identified also in Garcinia mangostana (Hypericaceae) [22]. Cinnamic acid, benzoic acid, m-hydroxybenzoic acid and malonic acid were found to be efficient precursors of this compound [22].…”
Section: Hypothetical Biosynthesis Pathway Of Xanthonesmentioning
confidence: 93%
“…1, compound 7) was identified also in Garcinia mangostana (Hypericaceae) [22]. Cinnamic acid, benzoic acid, m-hydroxybenzoic acid and malonic acid were found to be efficient precursors of this compound [22]. Beerhues and coworkers [21,23] have studied also the biosynthesis of xanthones in H. androsaemum cell suspensions.…”
Section: Hypothetical Biosynthesis Pathway Of Xanthonesmentioning
confidence: 99%
“…Benzophenones are the immediate precursors of xanthones in higher plants, as shown by feeding experiments with differentiated plant organs [1][2][3]. In addition, 2,3',4,6-tetrahydroxybenzophenone was recently found to be converted regioselectively to isomeric xanthones in cell-suspension cultures of Centaurium erythraea and Hypericum androsaemum (Peters, Schmidt and Beerhues, unpublished results).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding experiments with intact plants of Garcinia mangostana (Hypericaceae) have shown that m-hydroxybenzoic acid is an efficient precursor of xanthone biosynthesis [3]. This appeared to be also true for xanthone formation in cultured cells of C. erythraea because these accumulate, when treated with a yeast extract, 1,5-dihydroxy-3-methoxyxanthone [6] the 5-hydroxy group of which corresponds to the 3-hydroxy group of m-hydroxybenzoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthetic origin of the hydroxybenzoyl-CoA precursor (11) of xanthones is subject to controversy. Thus, 14 C-labelled phenylalanine (7) was reported to be incorporated into xanthones from Gentiana lutea, albeit with low incorporation rates [10], and label from cinnamic acid and benzoic acid was diverted to the xanthone, mangostin, in Garcinia mangostana [11,12].…”
mentioning
confidence: 99%